Cardiovascular disease risk factors are associated with conventional lipids and apolipoproteins in South African adults of African ancestry - Anri Vorster; Ruan Kruger; Catharina MC Mels; Yolandi Breet (Lipids in Health and Disease)
Abstract Background Although conventional lipids (high density lipoprotein cholesterol (HDLC), low density lipoprotein cholesterol (LDLC), total cholesterol (TC) and triglycerides (TG)) are therapeutic targets to manage and prevent atherosclerotic cardiovascular disease (CVD), apolipoprotein (Apo) levels have sparked interest for their potential to improve CVD risk prediction. This study explored the relationships of traditional CVD risk factors with conventional lipids, as well as ApoA1, ApoB and its ratio (ApoB: ApoA1) in South African adults of African ancestry. Methods This study included 1697 adults (aged 29 to 94) from the Prospective Urban Rural Epidemiology (PURE) study. The CVD risk markers included body mass index (BMI), physical activity index, tobacco use, dietary fat intake, γ-glutamyl transferase (γGT) and glycated haemoglobin (HbA1C). Conventional lipids were measured in serum samples using standard methodology, while ApoA1 and ApoB were measured using a multiplex magnetic bead immunoassay. Results Stratified into tertiles of conventional lipid and Apo levels, trends emerged across multiple CVD risk markers, including BMI, tobacco use, fat intake, γGT and HbA1C levels. Higher tertiles of LDLC, TC, TG, ApoB and ApoB: ApoA1, along with the lowest tertiles of HDLC and ApoA1 exhibited higher prevalence of Type II diabetes mellitus (all p ≤ 0.024) and overweight or obesity (all except for TC, p ≤ 0.024). HDLC was negatively associated and LDLC, TC, and TG were positively associated with BMI (all p < 0.001) and HbA1C (all except for TC, p ≤ 0.005). Similarly, ApoA1 associated negatively with BMI (β=-0.067 (-0.125; -0.010), p = 0.022) and HbA1C (β=-0.071 (-0.122; -0.020), p = 0.007), while ApoB associated positively with BMI (β = 0.168 (0.117; 0.218), p < 0.001). The ApoB: ApoA1 showed positive associations with BMI (β = 0.213 (0.163; 0.263), p < 0.001) and HbA1C (β = 0.123 (0.074; 0.172), p < 0.001). Conclusions In South African adults of African ancestry, ApoA1, ApoB and ApoB: ApoA1 levels are associated with various established CVD risk markers and suggests that these apolipoproteins may provide additional mechanistic insights beyond the conventional lipids to understand the aetiology of early cardiometabolic disease development.